2011
DOI: 10.2514/1.j051060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamic Stall on the Aerodynamics of Vertical-Axis Wind Turbines

Abstract: Accurate simulations of the aerodynamic performance of vertical-axis wind turbines pose a significant challenge for computational fluid dynamics methods. The aerodynamic interaction between the blades of the rotor and the wake that is produced by the blades requires a high-fidelity representation of the convection of vorticity within the wake. In addition, the cyclic motion of the blades induces large variations in the angle of attack on the blades that can manifest as dynamic stall. The present paper describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The use of helical/twisted blades was found to improve turbine performance as compared to straight blade. This aerodynamic model was compared to experimental data by Scheurich and Brown [52] and Scheurich et al [53] and found to be in very satisfactory agreement based on blade aerodynamic loading and predicted power curves. The relatively fast computational time in comparison to using higher-fidelity CFD simulations is one of the main benefits of this method.…”
Section: 3mentioning
confidence: 81%
“…The use of helical/twisted blades was found to improve turbine performance as compared to straight blade. This aerodynamic model was compared to experimental data by Scheurich and Brown [52] and Scheurich et al [53] and found to be in very satisfactory agreement based on blade aerodynamic loading and predicted power curves. The relatively fast computational time in comparison to using higher-fidelity CFD simulations is one of the main benefits of this method.…”
Section: 3mentioning
confidence: 81%
“…These curves informed the selection of the tip speed ratio λ = 1.9 as the operating point for detailed near-wake characterisation. We expect that at this tip speed ratio the turbine blades will be operating in dynamic stall over a part of the turbine rotation, [27] reaching maximum angles of attack of approximately 35º, and that this will be a significant contributor to the near-wake structure. Note that the maximum power coefficient could likely be improved with simple geometric modifications, e.g., changing the blade pitch, [28] but for this study the geometry was meant to be as simple as possible, therefore the blade pitch was left at zero.…”
Section: Results and Discussion 31 Data Processingmentioning
confidence: 99%
“…For example, in a 2.5 MW wind turbine, simulated erosion experiments have shown that leading edge erosion can severely affect the airfoil performance to such an extent that, depending on the severity of erosion, up to 25% annual energy loss can be expected [10]. Other studies have confirmed the impact of surface roughness on aerodynamic force coefficients and stall characteristics [11,12,13,14] and consequently on aerodynamic performance [15,16] as well as dynamic instabilities [17]. Evidence of leading edge erosion can be found on the blades' surface in as early as two to three years after installation [5,18].…”
Section: Introductionmentioning
confidence: 94%